Manifestasi Perilaku Belajar bagi Perkembangan Self Esthem Santri - Arifia Retna Yunita (At- Ta'lim : Jurnal Pendidikan, 2021)
Modern Islamic boarding schools are educational instutions that are still developing in the world of education, student at a muslim school have more time than students because they get the two learning opportunities at school and in the islamic boarding school. Students learn and manifest their learning behavior with habits, skill, observation, rational nad critical thinking, attitude, inhibition. Appreciation of manifestations that affect the development of self esteem is belief, the ability to act and face life’s challenges, belief in happiness, a feeling of worthiness. The research method used is a literature approach that examines a variety of literature relevant to the topic of study